Washing the guilt away: effects of personal versus vicarious cleansing on guilty feelings and prosocial behavior - Xu, Hanyi; Bègue, Laurent; Bushman, Brad (Frontiers in Human Neuroscience, 2014)
For centuries people have washed away their guilt by washing their hands. Do people need to wash their own hands, or is it enough to watch other people wash their hands? To induce guilt, we had participants write about a past wrong they had committed. Next, they washed their hands, watched a washing-hands video, or watched a typing-hands video. After the study was over, participants could help a Ph.D. student complete her dissertation by taking some questionnaires home and returning them within 3 weeks. Results showed that guilt and helping behavior were lowest among participants who washed their hands, followed by participants who watched a washing-hands video, followed by participants who watched a typing-hands video. Guilt mediated the effects of cleansing on helping. These findings suggest that washing one’s own hands, or even watching someone else wash their hands, can wash away one’s guilt and lead to more helpful behavior.